2013
DOI: 10.1038/bjc.2013.183
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus as second- or third-line treatment of advanced endometrial cancer: ENDORAD, a phase II trial of GINECO

Abstract: Background:Patients with recurrent/metastatic endometrial cancer that progresses after chemotherapy have limited treatment options and poor outcomes. Preclinical data suggest the oral mammalian target of rapamycin inhibitor everolimus may provide clinical benefit in these patients.Methods:In this multicenter, open-label, phase 2 study, patients with advanced or metastatic endometrial cancer refractory to one or two previous chemotherapy regimens received everolimus 10 mg per day until progression or unacceptab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 32 publications
(41 reference statements)
3
51
0
1
Order By: Relevance
“…This may be due to the high prevalence of insulin resistance in patients with endometrial cancer [34] as 14 patients (21%) in this trial had history of diabetes and/or hyperglycemia. The ORR observed with pilaralisib (6%) was consistent with Phase II trials with rapalogs in similar patient populations (ORR 0-11%) [16][17][18][19]35]. As single agents, temsirolimus, ridaforolimus, and everolimus have shown limited response rates between 0% and 14% depending upon the number of lines of prior chemotherapy, with more heavily pretreated patients having lower response rates [16][17][18][19].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This may be due to the high prevalence of insulin resistance in patients with endometrial cancer [34] as 14 patients (21%) in this trial had history of diabetes and/or hyperglycemia. The ORR observed with pilaralisib (6%) was consistent with Phase II trials with rapalogs in similar patient populations (ORR 0-11%) [16][17][18][19]35]. As single agents, temsirolimus, ridaforolimus, and everolimus have shown limited response rates between 0% and 14% depending upon the number of lines of prior chemotherapy, with more heavily pretreated patients having lower response rates [16][17][18][19].…”
Section: Discussionsupporting
confidence: 60%
“…PIK3CA mutations and PTEN deficiency have been demonstrated to correlate with poor prognosis in patients with endometrial carcinoma. In Phase II studies, rapamycin analog mTOR inhibitors everolimus, ridaforolimus and temsirolimus have shown evidence of clinical activity in advanced endometrial carcinoma [16][17][18][19]. New generation kinase inhibitors targeting the PI3K pathway are under evaluation in endometrial cancer, including pan-class I PI3K inhibitors such as BKM120, dual PI3K/mTOR inhibitors, such as GDC-0980, and the AKT inhibitor MK-2206 [6,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Objective response rates range from 0%-30% depending upon the clinical population; clinical response rates are higher in populations that have not received prior chemotherapy and response occurs across histologic subtypes including endometroid, high-grade papillary serous, and clear cell cancers. Importantly, there is a subset, albeit small, of patients with complete and/or durable responses (32)(33)(34)(35)(36)(37).…”
Section: The Rapalogsmentioning
confidence: 99%
“…AKT activation can result in activation of the mTOR signalling pathway providing a rationale for treatment with mTOR inhibitors [44]. In early clinical studies benefit is shown from mTOR inhibition, but there are no results from late-phase trials yet [45, 46]. Some endometrium tumours are highly mutated caused by a mutation in POLE [40].…”
Section: Discussionmentioning
confidence: 99%